Parental communication, language and personal social development of preschool children - Ardhiani, Innas Tiara; Aqidatuzzahro, Achsa; Sari, Dwi Puspita (Institute of Computer Science (IOCS), 2025)
The communication process between parents and children is essential, as children’s language and social development are influenced by communication patterns and interactions within the family. To prevent delays in language and social development, it is important to optimize communication between parents and children. This study sought to identify patterns of parental communication, language development, and personal-social development in preschoolers as well as the relationship between parental communication and the language and personal-social development of preschoolers at PAUD Bunga Pelangi, Polehan, Malang City. The research design used correlational analytics with a cross sectional approach conducted on a sample of 39 children and their mothers. The data collection tools used were in the form of a parental communication questionnaire with 20 statement items, and a Denver Development Screening Test (DDST) II sheet. The data was analyzed using the Spearman Rank Test. The results of the study showed that most children with positive parental communication had normal language and social personality development. With a p value of less than 0.05, the findings demonstrated a significant and fairly robust correlation between preschoolers' linguistic and social personality development and parental communication. Based on the results of the study, parents should optimize communication with children so that children's development, especially language and social personality development of preschoolers, can run optimally according to their age.